The Effect of Environmental Expenditures and Technology Development on Net Zero Emission - Fitriana Halimah, Annisa; Prasetyia, Ferry (Journal of Development Economic and Social Studies, 2025)
The high CO2 emissions from forest fires in Sumatra and Kalimantan in 2018 2023 are a challenge to achieve net zero emissions. The implementation of the Paris Agreement Framework through aspects of regional environmental spending and technological development is needed to control CO2 emissions to remain low throughout industrialization at the stage of economic development. This study aims to see the effect of environmental expenditure and technology development on achieving Net Zero Emission. The results show that environmental function expenditure, ICT infrastructure access, Population Density, and Agriculture Forestry GRDP have a significant effect on increasing CO2 emissions. Meanwhile, ICT expertise and use have a significant effect on reducing CO2 emissions. The research is addressed to provincial governments on the islands of Sumatra and Kalimantan and environmental policy makers as a consideration in developing a net zero emission 2045 strategy.